Review Of Equestrian Training (Equestrian Sports) On Athlete Concentration At Club Stable, Bahar Peat District - Nahan, Tiara Anggreani; Dirgantoro, Edwin Wahyu; Nurdiansyah, Nurdiansyah (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study examines the impact of equestrian training on the concentration levels of athletes at Club Stable Bahar, located in the Peat District. Recognising the unique cognitive demands of equestrian sports, this research investigates how structured training contributes to riders' mental focus and attentional capacity. The study employed a quantitative descriptive method, utilising observation techniques and validated questionnaires to collect data on athlete concentration levels. Six athletes from the club participated as respondents. The analysis categorised concentration levels into three groups: high, medium, and low. The results revealed that none of the athletes (0%) were in the high-concentration category, five athletes (83%) were in the medium category, and one athlete (17%) was categorised as having low concentration. These findings suggest that while equestrian training at Club Stable Bahar provides some cognitive stimulation, it may not be sufficiently structured to develop high-level concentration skills in most athletes. In conclusion, the overall concentration level of athletes engaged in equestrian training at Club Stable Bahar falls within the medium category. This highlights the need for the integration of targeted psychological skills training—particularly focused attention and mental conditioning—into the existing equestrian training programs. Enhancing these aspects may not only improve rider concentration but also positively influence overall performance and safety in equestrian sports. Further research with a larger sample size is recommended to validate these findings and develop evidence-based training models for cognitive skill development in grassroots equestrian settings.